Conservation law and exact solutions for ion acoustic waves in a magnetized quantum plasma - El-Kalaawy, Omar; Ibrahim, Rafat; Sadek, Lamyaa (International Journal of Applied Mathematical Research, 2016)
The head on collision of ion- acoustic solitary waves (IASWs) in a magnetized plasma are considered. The two- sides Korteweg-de Vries (KdV) equations in generic case as well as the two- sides modified Korteweg-de Vries (mKdV) equations in a special case are obtained.The analytical phase shifts and the trajectories after the Head-on collisions of two IASWs in a three species quantum plasma are derived by using the extended version of Poincare-Lighthill-Kuo (PLK) method for both the situations. The conservation laws for KdV and mKdV equations are obtained. By applying the extended direct algebraic method, we found the traveling wave solutions for the two-sides KdV and mKdV equations.